2021
DOI: 10.1186/s13063-021-05580-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a multidimensional versus usual care physiotherapy on pain and electroencephalography (EEG) spectrum in chronic nonspecific low back pain: study protocol for a randomized controlled trial

Abstract: Background Non-specific chronic low back pain (NSCLBP) is a major public health and global socioeconomic burden associated with a complex interplay of biopsychosocial factors. Despite scientific signs of progress, treatment of NSCLBP often tends to stick to a biomechanical model, without targeting psychological and social factors. To enhance the clinical efficacy of usual physiotherapy for NSCLBP, the development of clinical strategies is to be pursued. This study aims to assess the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This result corroborates that by Atemkeng et al (15) in Douala Cameroon, who observed a signi cant improvement in pain and mobility of the low back pain patients after 6 weeks of physiotherapy follow-up. Similarly, studies (18) in India and Iran (19) reported signi cant improvement in pain and disability after receiving conventional physiotherapy treatment. However, this result is in contrary to that reported by a systematic review on the effects of physical therapy rehabilitation on chronic non-speci c low back pain.…”
Section: General Description Of Populationmentioning
confidence: 76%
“…This result corroborates that by Atemkeng et al (15) in Douala Cameroon, who observed a signi cant improvement in pain and mobility of the low back pain patients after 6 weeks of physiotherapy follow-up. Similarly, studies (18) in India and Iran (19) reported signi cant improvement in pain and disability after receiving conventional physiotherapy treatment. However, this result is in contrary to that reported by a systematic review on the effects of physical therapy rehabilitation on chronic non-speci c low back pain.…”
Section: General Description Of Populationmentioning
confidence: 76%
“…This study was a 22-week, outcome assessor-blind, randomized, controlled, parallel trial from April 2020 to February 2022. The study protocol has been published previously [39] (Additional le 1). The ethical committee of the Iran University of Medical Sciences (IUMS) approved this study (IR.IUMS.REC.1398.1041).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…EEG signals were recorded under two conditions: three minutes of an eyes-open resting state and 20 seconds of active lumbar forward exion. The absolute and relative (percentage of total EEG power) EEG power spectra analyses of the following frequency domains were calculated: delta (1-3.8 Hz), theta (4.0-7.8 Hz), alpha (8.0-13.8 Hz), beta (14.0-34.8 Hz), and gamma (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Outcome Measuresmentioning
confidence: 99%